Legal Analysis of the Authority of the Supervisory Board in Law Number 19 of 2019 concerning the Corruption Eradication Commission - Hajuan, Ardi; Nurul Aini; Saifullah Fadel (Journal of Legal Contemplation, 2025)
This study is to determine the Authority of the Supervisory Board in Law No. 19 of 2019 concerning the Corruption Eradication Commission. Regarding the KPK Supervisory Board, with the authority to grant permission or not to grant permission for wiretapping, search and/or seizure, this shifts the concept of supervision to the concept of control in the implementation of the duties and authorities of the Corruption Eradication Commission. So that this is closely related to the independence of the Corruption Eradication Committee, which in carrying out its duties and authorities is independent and free from the influence of any power. The results of the study describe the juridical authority of the Supervisory Board in Law No. 19 of 2019 concerning the Corruption Eradication Commission and the authority of the Supervisory Board in a sociological perspective. The Supervisory Board is not a law enforcer, but is only tasked with overseeing the implementation of the KPK's duties and authorities. With the existence of the KPK Supervisory Board within the KPK, it is feared that it will hamper efforts to eradicate corruption.